Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Manafaktur Di Bursa Efek Indonesia - Rani Marthasari, Olivia; Gustiawaty Dewi, Fajar; Indah Oktanti Sembiring, Sari (GEMA EKONOMI, 2023)
Entering the era of globalization and increasingly competitive business competition, good Good Corporate Governance has become a fundamental need for companies. Although it has long been a prominent issue, the implementation of GCG has not been fully implemented in Indonesia in accordance with GCG principles, both state-owned companies and private companies. The implementation of GCG at this time is no longer just an obligation, but has become a necessity for every company and organization. GCG is needed to provide progress on the performance of a company, making the company long-lived and trustworthy. If a company has the trust of investors, then investors and other stakeholders will not hesitate to make investments that will cause the value of the company to increase. It's just that research on variations in the implementation of corporate governance at the company level is still very little done. From previous studies that proved different results, the author was motivated to conduct further research on how corporate governance affects financial performance as measured by Tobin's Q. This study complements the variables of previous research by adding variables, such as the proportion of independent board of commissioners, foreign ownership, managerial ownership, institutional ownership, independence of the audit committee, and The quality of the audit will be tested for its effect on the financial performance of non-financial services. The data needed in this study were obtained from ICMD, IDX website www.idx.co.id, and various other kinds of literature. Descriptive statistics are used to provide an overview or descriptive of a data seen from the average value, minimum value, maximum value, and standard deviation.